2020
DOI: 10.1097/wnr.0000000000001494
|View full text |Cite
|
Sign up to set email alerts
|

miR-132-5p regulates apoptosis and autophagy in MPTP model of Parkinson’s disease by targeting ULK1

Abstract: Parkinson’s disease (PD) is a neurodegenerative disorder that is characterized by a loss of dopaminergic neurons in the substantia nigra of the brain. Numerous investigations have focused on the underlying mechanism involved in the progression of PD in recent decades. miR-132 is abnormal expression in many diseases including PD. However, the functional role and molecular mechanism of miR-132-5p in PD pathogenesis are still not elucidated. In our study, we found miR-132-5p was upregulated in 1-methyl-4-pheny-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…of miR-132-5p, which is upregulated in MPTP-induced Pd models, decreases neuronal apoptosis and autophagy via direct targeting of ULK1, suggesting the enhancement of autophagy in miR-132-5p-mediated neurotoxicity in Pd (95). One explanation for this may be that miR-132-5p is involved in MPTP-stimulated overactivation of autophagy in neurons, ultimately leading to autophagic cell death.…”
Section: Neurotoxicity Of Mirnas By Regulating Autophagymentioning
confidence: 99%
“…of miR-132-5p, which is upregulated in MPTP-induced Pd models, decreases neuronal apoptosis and autophagy via direct targeting of ULK1, suggesting the enhancement of autophagy in miR-132-5p-mediated neurotoxicity in Pd (95). One explanation for this may be that miR-132-5p is involved in MPTP-stimulated overactivation of autophagy in neurons, ultimately leading to autophagic cell death.…”
Section: Neurotoxicity Of Mirnas By Regulating Autophagymentioning
confidence: 99%
“…Despite of very short half-life (<30 min) of ( R )-ketamine in rodents [ 27 ], ( R )-ketamine can elicit long-lasting (>7 days) prophylactic effects in LPS model [ 44 ] and CRS model [this study]. It is reported that inhibition of miR-132-5p increased cell survival ability and reduced MPTP (1-methyl-4-pheny-1,2,3,6-tetrahydropyridine)-induced apoptosis of SH-SY5Y cells, suggesting that miR-132-5p inhibition may be a potential therapeutic target for Parkinson’s disease [ 63 ]. Collectively, it seems that higher expression of miR-132-5p in the PFC might contribute to depression-like behaviors in CRS-exposed mice, and that inhibition of miR-132-5p could show antidepressant-like effects in CRS-exposed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Uridine at the 5′ end of miRNA, which can partially complement the 3′ untranslated region of mRNA, leading to in translation repression of the mRNA, thus, playing a vital role in post-transcriptional regulation of gene expression 60 . Numerous studies have unveiled that multiple mi-RNAs, including miR-372 61 , miR-93 62 , miR-142-5p 63 , miR-20a 64 , 65 , miR-106b 64 , miR-106a 66 , 67 , 68 , miR-26a/b 69 , miR-489 70 , miR-1262 71 , miR-214 72 , miR-214-3p 46 , miR-125b 72 , and miR-155 73 inhibit ULK1 gene expression by directly targeting the mRNA of ULK1 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 . In addition, microRNAs could also play an indirect role by regulating ULK1-related pathways.…”
Section: The Molecular Basis Underlying the Regulation Mechanism Of Ulk1mentioning
confidence: 99%